Pisces, Characiformes, Characidae, Glandulocaudinae, Mimagoniates barberi Regan, 1907: First Argentinean distribution record - Mantinian, Julia Erika (2010)
The current note reports the presence of Mimagoniates barberi at northeastern Argentina. This record represents the southernmost limit for this species and the first country record of the genus.